2020
DOI: 10.1136/bmjopen-2019-033391
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-wide ELectronic medical record evaluated computerised decision support system to improve outcomes of Patients with staphylococcal bloodstream infection (HELP): study protocol for a multicentre stepped-wedge cluster randomised trial

Abstract: IntroductionStaphylococci are the most commonly identified pathogens in bloodstream infections. Identification of Staphylococcus aureus in blood culture (SAB) requires a prompt and adequate clinical management. The detection of coagulase-negative staphylococci (CoNS), however, corresponds to contamination in about 75% of the cases. Nevertheless, antibiotic therapy is often initiated, which contributes to the risk of drug-related side effects. We developed a computerised clinical decision support system (HELP-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The idea for a contextualized guideline visualization emerged during the early stages of the development of a guideline-based CDSS for the treatment of specific bloodstream infections [ 9 ]. The context-specific visualization concept was evaluated as part of a formative usability test, and clinicians generally approved of it.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The idea for a contextualized guideline visualization emerged during the early stages of the development of a guideline-based CDSS for the treatment of specific bloodstream infections [ 9 ]. The context-specific visualization concept was evaluated as part of a formative usability test, and clinicians generally approved of it.…”
Section: Discussionmentioning
confidence: 99%
“…Managing the complexity of medical algorithms and guidelines is a core challenge for the successful establishment of guideline-based CDSSs. In addition, existing CDSS-related research projects (such as the study by Hagel et al [ 9 ] to use a CDSS for the treatment of bloodstream infections) stressed the need—and critical effort—to obtain regulatory approval as a certified medical device (especially under the Medical Device Regulation). Establishing organizational as well as technical structures to qualify for the respective regulatory approval is inevitably necessary to use the concept in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that an adherence to treatment guidelines and particularly infectious disease bedside-consultation can lead to a reduction of mortality by up to 50% ( 10 12 ). Given the limited availability of infectious diseases physicians, who are usually based in larger hospitals and the standardized management outlined above, novel approaches are currently under investigation, such as computerized decision support systems and phone consultations, to improve outcome by providing respective expertise also in smaller hospitals ( 80 , 81 ). However, it has yet to be proven whether these approaches are as effective as bedside-consultations by infectious diseases physicians.…”
Section: Current Quality Evidence and Open Questionsmentioning
confidence: 99%